Multi-scale damage modeling in a ceramic composite using a Finite Element Microstructure Meshfree methodology - Marrow, T; Saucedo Mora, L (Royal Society, 2016)
The problem of multi-scale modelling of damage development in a SiC ceramic fibre reinforced SiC matrix ceramic composite tube is addressed, with the objective of demonstrating the ability of the FEMME (Finite Element Microstructure Meshfree) model to introduce important aspects of the microstructure into a larger scale model of the component. These are particularly the location, orientation and geometry of significant porosity and the load-carrying capability and quasi-brittle failure behaviour of the fibre tows. The FEMME model utilises finite element and cellular automata layers, connected by a meshfree layer, to efficiently couple the damage in the microstructure with the strain field at the component level. Comparison is made with experimental observations of damage development in an axially-loaded composite tube, studied by X-ray computed tomography and digital volume correlation. Recommendations are made for futher development of the model to achieve greater fidelity to the microstructure.